Lichen planopilaris in children: report of two cases. - Rodriguez-Lechtig, B.; Estrada, M.N.; Bocanegra, M.F.; Ocampo, M.A.; Sánchez, B.F.; Motta, A. (European Journal of Pediatric Dermatology, 2025)
Lichen planopilaris (LPP) is an uncommon cause of primary cicatricial alopecia in children, often underrecognized due to its rarity in this age group. We report two cases of LPP in male patients under 10 years of age, both presenting with scarring alopecia of the vertex, perifollicular erythema, and absence of follicular ostia on trichoscopy. In both cases, LPP was diagnosed and managed with topical corticosteroids. Drawing from these cases and available literature, we propose a practical diagnostic algorithm to support clinicians in identifying pediatric LPP early. This tool may facilitate accurate diagnosis, help differentiate LPP from other causes of patchy alopecia, and enable timely treatment to prevent irreversible hair loss.